Structural investigations on nanocrystalline Ni-W alloy films by transmission electron microscopy - Klimenkov, Michael; Haseeb, A.S. Md. Abdul; Bade, Klaus (Elsevier, 2009)
Electrode posited Ni-W alloys have been investigated in the as-deposited state by transmission electron microscopy in order to investigate the microstructural features in dependence of the tungsten content. Within the tungsten content range from 7 at. up to 12 at., the microstructure is nanocrystalline characterized by a bimodal grain size distribution, consisting out of 20 to 200 nm sized grains and also larger grains with several 100 mm characteristic dimension. No clear trend in microstructure formation is visible with W content or deposition conditions in the investigated W content range. Only solid solution phase characteristics were observed. The lattice constant is 0.360 nm for 12 at. W as derived from electron diffraction for the solid solution face centered cubic structure. Larger grains show twinning and stacking faults. Voids with diameter of a few nm were detected along with some multiple twinned particles. indicating high stress level during growth. About 2 at. difference in the alloy composition from grain to grain was measured. (C) 2009 Elsevier B.V. All rights reserved.